A diachronic study of the conative alternation construction in english - Esteban-Segura, María Laura; Salles-Bernal, Soluna (My University, 2017)
The conative alternation is a subtype of transitivity alternation in which there is a transitive variant and an intransitive one represented with an at-construction. From a syntactic point of view, it occurs with transitive verbs and is therefore referred to as a case of preposition insertion (the preposition at is inserted before the direct object). From a semantic perspective, it can be described as a “detransitivizing” construction, since there is a contrast between conative uses of transitive verbs and their transitive counterparts (Perek 2015: 90). Accordingly, the argument can be direct (subject, direct object or indirect object) or oblique. (1) a. Kim cut the pie. b. Kim cut at the pie (drunkenly) (Beavers 2006: 6). The patient (“the pie”) can have two realizations: as the direct object (1a) or as an oblique signalled by the preposition at (1b). Here we find a semantic contrast: in the transitive variant the patient is known to have been affected in some way, whereas in the one with the at-construction this is not necessarily the case; thus, the action denoted by the verb may or may not have been completed and the alternation may convey “a reduced a degree of effectiveness” (Riemer 2010: 354), as seen in example (2b) below, which implies that the action was not completely successful: (2) a. The zombies slashed my face. b. The zombies slashed at my face. Although the construction has been studied before (van der Leek [1996], Broccias [2001, 2003], Beavers [2010], Perek and Lemmens [2010], Guerrero-Medina [2011], Perek [2015]), it remains scarcely investigated from a diachronic point of view. Therefore, our main objective is to research on the origin and development of the conative construction in English by looking at its occurrence in several historical corpora. For the purpose, we have first made a comprehensive list of verbs which allow the construction and then selected the verbs under study. A collostructional analysis, which “investigates which lexemes are strongly attracted or repelled by a particular slot in the construction (i.e. occur more frequently or less frequently than expected)” (Stefanowitsch and Gries 2003: 214), has been carried out as it can help to establish which verbs favour the construction over others in the different corpora. Some of our preliminary results show that the construction was already present in Old English and that in most instances the subject is agentive or animate.
Keywords: Inglés - Transitivo; Conative alternation; Verb alternation; History of English; Collostructional analysis